PERAN BIDAN DALAM PEMBERIAN KONSELING PADA PELAKSANAAN ANTENATAL CARE (ANC) DI PUSKESMAS - Florentina Kusyanti (Dian Nuswantoro Semarang, 2022)
Pregnancy is a gift to be grateful for, but pregnancy is a condition of a person who is very vulnerable to a disease, psychology because during pregnancy there are many changes in the mother due to hormonal influences so that it requires the attention of both the family and health workers who are entitled to provide services. This study aims to find out how the role of midwives in counseling in the implementation of integrated Antenatal Care (ANC) at the puskesmas. The design of this study was qualitative with observations and interviews. that the age of the majority of respondents aged between 40-50 years amounted to 71.43%, Education Most had DIV education 42.86% Length of work Most of the years worked between 26-35 years amounted to 42.86%. but still done by the midwife. The conclusion is not all midwives provide counseling to pregnant women during integrated ANC services.